A review of leishmania genome, hosts, virulence factors, pathogenesis and treatment (World Journal of Current Medical and Pharmaceutical Research, 2024)
The study aims in this review to study the Leishmania genus parasite that causes Leishmaniasis, in its clinical forms Cutaneous Leishmaniasis (CL), MucocutanousLeishmaniasis (ML) and Visceral Leishmaniasis (VL). When studying the parasite's genetic composition of the genome of the nucleus and the genome of the kinetoplast, which constitutes 10-20% of the total DNA, it was found that despite the difference in pathogenicity between the types of the parasite L., the genetic material is similar and maintains the genetic content. CL is a self-healing disease, but prompt treatment is important to avoid unattractive scarring and parasite spread. Of all the drugs of choice, Pentostam and Glucantime are the first line of treatment for all types of leishmaniasis, but there are serious attempts to discover new therapies.